A NEW APPROACH IN EDUCATION: “COMBINING MIND MAPS AND ARTISTIC ACTIVITIES IN VOCATIONAL SKILL EDUCATION” - KOSALI , Oğuzhan; KOSALI, Başak (IKSAD JOURNAL, 2022)
In order to meet the need for qualified and trained staff in our country, vocational high schools have great responsibility. In order to decrease this need, vocational high school students should gain a high level of professional knowledge and competences. In addition, it is very important that vocational high schools achieve the developing technology and Industry 4.0 targets. With this study, it is aimed to develop a new teaching method and technique besides the existing methods in vocational knowledge courses. This research was carried out to determine that there are problems in the acquisition of professional skills and competences of students between the ages of 13-18 in vocational high school. This study was carried out since it was seen that theoretical knowledge and applied procedures in vocational knowledge courses could not complement each other and that modern techniques and technologies could fall behind while acquiring professional skills. There are problems in students' critical thinking, comprehension of the piece-whole relationship and problem-solving approaches. In addition, there are deficiencies in the persistence of professional skills and competences. In line with the objectives of the study, the readiness of the students will be revealed by using mind maps before starting to gain new skills and knowledge in vocational knowledge courses in order to bring analytical approaches to critical thoughts and problems. Students will be asked to create an individual mind map within the first 10 minutes of the course activities. This research will be applied at the 10th grade level formed by the choice of field in vocational high schools and at the 11th grade level formed by the choice of branch. In order to provide permanent learning and to make mental inferences, each student will express what he / she imagines about the professional skills and knowledge that will be gained in the first 10 minutes after the application of the mind map to actively use multiple sensory organs. Then the students will associate this art element with the mind map they have made before. This method will continue periodically weekly to relate to the subject of each professional knowledge course. As a result of all our studies, it has been demonstrated that progress has been achieved in terms of achieving lasting learning and increasing professional success levels. According to the results of the evaluation of daily activities and general evaluation, a positive picture has been developed.